Performance Response Tests on a New MFR Relay for AC Microgrids - , M. A. Aminu (Archives of Current Research International, 2019)
This paper presents the results of offline and online performance tests on a new multivariable fuzzy rule-based (MFR) relay for ac microgrids. The relay is based on measurement of four critical parameters (P, Q, V and I) and fuzzy logic implementation of rules framed on the basis of these parameters. The online test was performed by connecting the relay to a utility-microgrid testbed. The offline test was performed by simulating High, Normal and Low states of the critical parameters using proper combination of digital signal sources to implement short circuits (SCs) in SIMPOWERSystems®. In both offline and online tests, the faults simulated are standard SCs in the utility and microgrid. The results of both offline and online tests are similar, and show that the MFR relay outputs logic 1 during SC faults. The relay also outputs logic 0 before and after the SC faults for both offline and online tests.